2008
DOI: 10.1073/pnas.0800028105
|View full text |Cite
|
Sign up to set email alerts
|

The tactile integration of local motion cues is analogous to its visual counterpart

Abstract: The visual and somatosensory systems have been shown to process spatial information similarly. Here we investigate tactile motion processing using stimuli whose perceptual properties have been well established in vision research, namely superimposed gratings (plaids), barber poles, and bar fields. In both modalities, information about stimulus motion (speed and direction) conveyed by neurons at low levels of sensory processing is ambiguous, a conundrum known as the aperture problem. Our results suggest that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…Our observation of effects in early sensory areas is intriguing when considering psychophysical evidence that the somatosensory system computes stimulus features such as orientation of edges and motion in a similar manner as the visual system Pei et al, 2008Pei et al, , 2010Pei et al, , 2011. This similarity between the two sensory systems could allow for motion signals to be integrated at an early level in the processing hierarchy.…”
Section: Motion Congruence Enhances Gba In Visual and Somatosensory Cmentioning
confidence: 78%
“…Our observation of effects in early sensory areas is intriguing when considering psychophysical evidence that the somatosensory system computes stimulus features such as orientation of edges and motion in a similar manner as the visual system Pei et al, 2008Pei et al, , 2010Pei et al, , 2011. This similarity between the two sensory systems could allow for motion signals to be integrated at an early level in the processing hierarchy.…”
Section: Motion Congruence Enhances Gba In Visual and Somatosensory Cmentioning
confidence: 78%
“…To form a global motion percept, the tactile system spatially integrates the local motion signals provided by primary afferents across the skin [4]. Accordingly, Pei and colleagues showed that the perceived direction of motion of a plaid surface (i.e., a surface formed by superimposing two gratings of different orientations) is the result of spatial integration of the different local motion components [5]. Conversely to decode the motion path of an object sliding over a fixed area of the skin, direction and speed information, which are directly available to the nervous system [6][7][8][9], would need to be integrated over time.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the direction signal conveyed by these neurons was invariant with other stimulus properties, including not only shape, but speed and amplitude as well. Steve and colleagues then measured the neuronal responses evoked by tactile analogs of stimuli that had been used to probe visual motion processing, including gratings, barberpoles, and random dot displays (Pei et al, 2008(Pei et al, , 2010(Pei et al, , 2011.…”
Section: Steven Hsiao: In Memoriammentioning
confidence: 99%